VD_FINDINFO HC / 2012 / 297 vom 13. März 2012 - VD Tribunal cantonal (2012)
MESURE PROVISIONNELLE, ACTION EN PAIEMENT D'ENTRETIEN, MAJORITÉ{ÂGE}, ENFANT, OBLIGATION D'ENTRETIEN | 277 al. 2 CC, 261 al. 1 CPC (CH), 303 al. 1 CPC (CH), 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH), 310 CPC (CH), 317 al. 1 CPC (CH)